Self-Harm Tendencies: Early Detection and Preventive Strategies for University Students - Nasution, Jamilah Aini; Bahri, Syaiful; Rosita, Dara; Zuliani, Hetti (Universitas Mercu Buana Yogyakarta, 2025)
University students who are beginning to enter the early developmental stage as adults are in the process of being able to respond wisely to negative emotions that interfere with their practical lives. This study aims to identify the tendency of university students to engage in self-harming behaviour. The approach used in this research is quantitative-descriptive. The population of this research is Syiah Kuala University students, and the sampling technique is a cluster. The sample selection considers the faculty with the lowest Institutional Development Contribution (SPI) level at Syiah Kuala University. So, the number of research samples is 348 students. The research data was collected using a scale prepared by considering the items on the NSSI Ideation Questionary (NIQ) Items Within During Ideation Factor (Wilson, 2008) to determine the condition of self-harm tendencies. Based on the results of data analysis, it is known that there are 7% of respondents who do not have self-harm tendencies. While 74% of respondents have low levels of self-harm tendencies, and 14% of respondents are at moderate levels. However, it is of concern that there are 6% of respondents who have high and very high levels of self-harm tendencies. To prevent the tendency from increasing and possibly becoming self-harming behaviour, it is necessary to create a basic service program as a prevention effort at the university level